2000
DOI: 10.1080/026782900750018555
|View full text |Cite
|
Sign up to set email alerts
|

Novel mesophases in fluorine substituted banana-shaped mesogens

Abstract: A new homologous series of achiral banana-shaped mesogens ('Dn') has been synthesized and studied by the classical techniques (optical microscopy, diOE erential scanning calorimetry, X-ray diOE raction, miscibility studies and electro-optic investigations). The short homologues (D6-D8) exhibit a two-dimensional phase 'B1 x ' diOE erent from a B1 phase with a rectangular lattice. The longer homologues (D9-D14) present a mesophase which displays the defects of the B7 phase of the PIMB-NO 2 compounds. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 11 publications
1
76
1
Order By: Relevance
“…It has also been recently shown that columnar mesophases made of broken layers can have spontaneously ordered dipoles if made of so-called banana molecules. [4][5][6][7][8] Due to their bent-core shape, these molecules cannot rotate freely around the long axis (a line joining the banana ends) and the steric hindrances result in ordering of the dipole moments. The spontaneous polarization in the broken-layer, columnar banana phase can be either perpendicular to the column axis (the B 1 phase [4] with p2mg symmetry) or parallel to the column in the B 1Rev -type phases ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recently shown that columnar mesophases made of broken layers can have spontaneously ordered dipoles if made of so-called banana molecules. [4][5][6][7][8] Due to their bent-core shape, these molecules cannot rotate freely around the long axis (a line joining the banana ends) and the steric hindrances result in ordering of the dipole moments. The spontaneous polarization in the broken-layer, columnar banana phase can be either perpendicular to the column axis (the B 1 phase [4] with p2mg symmetry) or parallel to the column in the B 1Rev -type phases ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the connecting groups on the phase behavior was also investigated in detail, and it was found that the sequence of the connecting groups has a decisive role on the mesophase formation. [9] Also, the number of aromatic rings in the bent core has been varied. Symmetrical bent-core mesogens with either five [10] or seven [11][12][13][14][15][16] aromatic groups have been prepared with a great variety of mesophase properties.…”
Section: Introductionmentioning
confidence: 99%
“…When sandwiched between two glass plates, compound 7b displays a stripe-like texture appearing from the isotropic melt, which on further cooling grows slowly and fills up the whole field of view with circular domains (Figure 1). This is a typical texture of a B2 phase [23]. All the other higher homologues (C 14 , C 18 ) exhibit a similar type of texture.…”
Section: Resultsmentioning
confidence: 67%
“…The X-ray diffraction diagram (Figure 4) of compound 7b [23] shows three sharp lamellar reflection peaks in the small angle region with a 2 value of 2.08 (d 1 ¼ 42.43 Å ), 4.02 (d 2 ¼ 21.96 Å ) and 5.98 (d 3 ¼14.77 Å ), respectively, and a broad diffuse peak in the wide angle region centred at d-spacing of 4.58 Å due to the liquid-like co-relation of the molecules. The molecular length (L ¼ 65.86 Å ) was calculated by molecular modelling (by DFT ¼ B3LYP calculation using 6-31G basis set), assuming the molecules have a fully stretched conformation.…”
Section: Resultsmentioning
confidence: 99%